Effectiveness of Intravenous Magnesium Sulfate in Children Presenting to the Emergency Department with Acute Exacerbation of Asthma : Effectiveness of Intravenous Magnesium Sulfate in Asthma - Ehsan, Shaista; Haresh, Sindhu; Haider Tarar, Saba (Pakistan Journal of Health Sciences, 2023)
Asthma is a serious medical condition in the pediatric age group and can have a high mortality, therefore it should be managed effectively. Patients not responding adequately to first line therapy need additional treatment. A few research studies have evaluated the use of intravenous magnesium sulfate in improving respiratory scores in severe acute pediatric asthma but the results have been conflicting. Objectives: To determine the benefit of intravenous magnesium sulfate in treating children presenting with worsening of asthma symptoms. Methods: A cross-sectional prospective study carried out at the Pediatrics Unit of Zia Uddin University Hospital, Karachi from 1st March 2021 to 1st March 2022. On the whole, 280 children in the age group 2-12 years with acute worsening of asthma of were selected by non-probability purposive sampling technique, however, children in need of invasive ventilation and those having asthma related complications on radiological investigations were omitted. Chi-square was applied for categorical variables and a p-value <0.05 was considered statistically significant. Results: Out of 280 patients who came to the Pediatric Emergency Department with acute severe asthma, 236 (84.3%) patients responded to a single dose of intravenous magnesium sulfate manifested by an improvement in clinical asthma score, while 44 patients (15.7%) did not show improvement. The admission rate to the pediatric intensive care unit was only 12.8%. Conclusion: Magnesium sulfate infusion helps improve respiratory symptoms in acute worsening of pediatric asthma.